Bio-electrical impedance phase angle and impedance ratio as predictors of disease severity among critically ill children - Priyadarsini Samanta; Sruti Mohanty; Ipsa Mohapatra; Sibabratta Patnaik; Laxman Kumar Senapati; Barsha Baishali Parida; Pratyush Kanungo; Jayanti Mishra (Elsevier, 2024)
Objective: To find out the predictive ability of bio-electrical impedance analysis (BIA) phase angle and impedance ratio for disease severity/mortality among critically ill children. Methods: A prospective observational study, among eighty-one children admitted to pediatric intensive care unit (PICU) was undertaken. Using bioelectrical impedance analyzer, phase angle (PA) and impedance ratio (IR) were recorded. Pediatric index mortality score (PIM3) was used to assess disease severity and mortality. Length of hospital stay (LOS), 30-day mortality, demographic and anthropometric measurements were recorded. Results: Mean age of the patients was 4.11 ± 4.60 years, majority were males (54.32 %). Mortality was 6.2 %. IR was significantly lower among survivor group than non-survivor group, while rest of the variables were comparable. The mean PIM3 score was lower (12.71 ± 7.39) among survivors than non-survivors (14.56 ± 5.56). Receiver operator characteristic (ROC) curve analysis showed a cutoff of 3.9° PA predicted the mortality with sensitivity of 93 % and specificity of 86.8 %. At a cutoff of 0.879, IR predicted the mortality with sensitivity and specificity of 93 %. The LOS increased with disease severity, and this difference was statistically significant. Although the mean LOS among survivors was less in comparison to the non-survivors; this difference was not statistically significant. Conclusions: Bio-electric impedance PA and IR at the time of PICU admission can be used as an independent predictor of disease severity and 30-day mortality and can be a prognostic marker. Further multicentric studies with large sample size can strengthen our study findings.